Wednesday

August 27, 2014

August 27, 2014

Posted by **Yania** on Saturday, April 6, 2013 at 6:11pm.

- math -
**Leo**, Saturday, April 6, 2013 at 6:37pmAll you need to do is substitute -3 in place of the x.

- math -
**Ollie**, Saturday, April 6, 2013 at 6:39pmsubstitute -3 for every x in f(x) and simplify.

- math -
**Steve**, Sunday, April 7, 2013 at 6:21amby now you've probably done it, but watch the "-" signs carefully

f(-3) = -8 * (-3)^2 = -8(9) = -72

**Related Questions**

math grade 11 - A quadratic function is defined by f(x)= 3x^2+4x-2. A linear ...

math grade 11 - A quadratic function is defined by f(x)= 3x^2+4x-2. A linear ...

Let f be the function be defined by f(x)=5^((2x^2) - Let f be the function be ...

Calculus - A cubic polynomial function f is defined by f(x) = 4x^3 + ax^2 + bx...

Calculus - A cubic polynomial function f is defined by f(x) = 4x^3 + ax^2 + bx...

Algebra - Today I did a practice SAT problem. If the function ƒ is defined by...

Maths - Correct each of the following incorrect statements: 1)The inverse of the...

calculus - For x including [–15, 13] the function f is defined by f(x)=x^7(x+4)^...

math-calc - for x (-12, 10) the function f is defined: f(x)=x^7(x+2)^2 On which ...

For the function defined by...HELP - For the function defined by f(x)=3x^2+5x+2...